Salivary proteomic profile of response to different resistance training protocols: A case report - Santos, Karina Oliveira; Filho, Dalton Muller Pessôa [UNESP]; Ventura, Talita Mendes Oliveira; Thomassian, Larissa Tercilia Grizzo; Macedo, Anderson Geremias [UNESP]; Buzalaf, Marília Afonso Rabelo; Braga, Aline Silva; Faria, Murilo Henrique [UNESP]; Magalhães, Ana Carolina (Wiley, 2024)
Resistance training (RT) with blood flow restriction (BFR) or high intensity (HI) are effective to increase muscle mass. To understand this effect, techniques known as “omics” are used to identify possible biomarkers. This study analyzed the salivary proteomic profile of healthy individuals trained before and after two RT protocols both designed with eight exercises for upper- and lower-limbs, one performed at low percentage of one-maximum repetition (%1RM) with BFR technique, and other at high %1RM (HI) without BRF technique. Four healthy males between 18 and 28 years participated in the study. Stimulated saliva was collected before (BBFR/BHI) and immediately after (ABFR/AHI) the two RT protocols. All protein-related processing was performed using label-free proteomic. The difference in expression between groups was expressed as p <.05 for downregulated proteins and 1-p >.95 for upregulated proteins. There was difference in salivary flow between ABFR and BBFR (p =.005). For HI, 87 proteins were found after the practice and 119 before. Three hemoglobin isoforms were increased in AHI compared with BHI. In the BFR comparison, 105 proteins were identified after (ABFR) and 70 before (BBFR). Among those increased ABFR, we highlight five hemoglobin isoforms and Deleted in malignant brain tumors 1 protein. Between ABFR and AHI, 17 isoforms of histones, Transaldolase, Transketolase, Glyceraldehyde-3-phosphate dehydrogenase, and Antileukoproteinase were decreased ABFR. For HI, there was an increase in proteins related to oxidative stress and metabolism of the musculoskeletal system, compared with BFR. HI seems to induce higher anabolic signaling to muscle mass increase and antiatherosclerotic effects.
Keywords: biomarkers; molecular biology; occlusion training; strength training